Why Gender Mainstreaming Fails at the Local Level: A Policy Capacity Analysis of Human Development Policy in Wonogiri Central Java - Hanani, Retna; Rosilawati, Risky Shinta; Bellastuti, Damaris Bernike (Badan Riset dan Inovasi Daerah Provinsi Jawa Timur, 2025)
This study examines the failure of gender mainstreaming policies in the context of regional development in Indonesia. Using evidence from Wonogiri which has a significant gap in the Human Development Index (HDI) between men and women, this study examines the failure of gender mainstreaming policy implementation at the regional level. Qualitative research methods are applied through document analysis and in-depth interviews with local policy actors. The results show that although gender mainstreaming is a national mandate, its implementation at the regional level is symbolic, uncoordinated, and hampered by technical limitations and weak political will. These findings highlight that institutional fragmentation and decentralized governance structures are major obstacles to achieving gender equality. In conclusion, strengthening local policy capacity is needed so that gender mainstreaming can function as a substantive instrument in promoting equitable and inclusive development.